Risk factors and outcomes of antibiotic-resistant Klebsiella pneumoniae bloodstream infections in adult patients with acute leukemia - Juan Wu; Zhiqiang Xie; Xueyu Li; Kaili Du; Zhongxian Liao; Yawei Shi; Munire Abudumaijiti; Jiadi Chen; Yingping Cao; Xinmiao Fu (BMC Microbiology)
Abstract Background Bloodstream infections (BSIs) caused by Klebsiella pneumoniae (K. pneumoniae) are a serious risk for patients with acute leukemia (AL), especially in the context of the increasing global prevalence of antibiotic-resistant strains. This retrospective study aimed to explore the risk factors for and outcomes of BSIs caused by antibiotic-resistant K. pneumoniae strains among AL patients. Methods This retrospective cohort study included patients with AL who suffered from K. pneumoniae BSIs from January 2017 to March 2024. Multivariate cox proportional hazards regression models were constructed to identify independent predictors of mortality. A Kaplan-Meier curve was used to evaluate the clinical outcomes of AL patients. Results The study included 122 AL patients with K. pneumoniae BSIs. Multivariate analysis revealed that the previous use of quinolone, cephalosporin or aminoglycoside was an independent risk factor for carbapenem-resistant (CR) K. pneumoniae BSIs. Similarly, previous use of carbapenem or cephalosporin and hospitalization duration were independent risk factors for extended-spectrum β-lactamase (ESBL)-producing K. pneumoniae BSIs. Furthermore, the previous use of corticosteroids could prevent the development of CR K. pneumoniae BSIs and ESBL-K. pneumoniae BSIs. Previous treatment with quinolones, cephalosporins, and aminoglycosides independently contributed to the risk of multidrug-resistant (MDR)-K. pneumoniae BSIs. The 30-day mortality rate among these AL patients was 23.77%. The 30-day mortality rates for AL patients with MDR-K. pneumoniae BSIs and non-MDR-K. pneumoniae BSIs were 42.5% and 13.79%, respectively. Similarly, the CR of K. pneumoniae and ESBL-producing K. pneumoniae also increased the 30-day mortality rate among AL patients with K. pneumoniae BSIs. Multivariate analysis revealed that MDR-K. pneumoniae BSIs and age ≥ 55 years were independent risk factors for 30-day mortality. Conclusions Previous antibiotic exposure is a key risk factor for the development of antibiotic-resistant K. pneumoniae BSIs among AL patients. MDR K. pneumoniae BSIs and age older than 55 years were independent risk factors for 30-day mortality among AL patients with K. pneumoniae BSIs.